Driving Towards Digitalization and Industry 4.0 in the Coal Mining Sector - Ayeisha, Bthari; Anggoro, Yudo (Universitas Mercu Buana, 2024)
This research provides an in-depth analysis of the impact of digitalization on the coal mining sector, with a special focus on PT X. The study employs a combination of content analysis, narrative analysis, and business solution mapping to extract insights from interviews conducted with five key stakeholders at PT. X. The objective is to assess how technological advancements can elevate operational efficiency and competitiveness in the era of Industry 4.0, and to identify strategies for effectively reducing reliance on human resources in site monitoring, while ensuring employee satisfaction and smooth transition. Through the methodological triangulation of content and narrative analysis, the study distils crucial themes and perspectives from the interviews. It identifies that the integration of advanced technologies like IoT, data analytics, and automation is vital for enhancing operational efficiency and reducing operational downtime. The research highlights the importance of transitioning from manual to automated site monitoring, emphasizing the adoption of drones and automated systems to bolster operational accuracy and efficiency. A key finding of the study is the identification of potential obstacles in digital technology investment, such as cost, system integration challenges, and employee resistance to new technologies. The study suggests that overcoming these barriers requires effective communication strategies and comprehensive training programs for employees. Drawing on the successful digital transformation strategies of companies like Adaro, the research recommends that PT. X should adapt similar strategies, customized to its unique challenges and context. The study contributes valuable insights into the digital transformation process in the coal mining sector, offering practical recommendations for companies like PT. X navigating the complex landscape of Industry 4.0.